Kurasi Data dalam Laman Sarawakiana oleh Pustaka Negeri Sarawak - Awang Arif Syamim, Awang Abdul Rahman (Universiti Malaysia Sarawak (UNIMAS), 2020)
This study is about the Curating Online Data in Sarawakiana Collection by Sarawak State Library. This study was conducted to identify the curatorial role in data curation for the collection and to document the curation method in the digital platform used by the Sarawakian Collection. The study was conducted using qualitative methods, interviews and observations on the Sarawakian Collection website as well as from scientific sources such as books, and journals. This study found out the curatorial role in the care of the online collection and arranging of work. The researcher will determine whether the care of the Sarawakina Collection by a curator and the role of the curator in arranging the Sarawakina Collection.